2019
DOI: 10.1016/j.spinee.2018.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Frailty status as a predictor of 3-month cognitive and functional recovery following spinal surgery: a prospective pilot study

Abstract: This pilot study demonstrates a trend toward poorer cognitive recovery 3 months following elective spinal surgery for frail patients. Frailty screening can help preoperatively identify patients who may experience protracted cognitive and functional recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 27 publications
(31 reference statements)
0
43
0
2
Order By: Relevance
“…* * Surgeries were all ACDF confirmed during the study by operative report and postsurgical radiographs. 6 Rehabilitation Research and Practice lumbar spinal stabilizer training combined with behavior or cognitive therapy) was included in several of these studies as behavioral or cognitive training has been shown to help improve recovery from spine surgery [12,37,38]. Given recent motor control studies specify 8 or more weeks necessary to integrate strength changes with spine stabilizers, so that 12 weeks may have not been a long enough follow-up time to see differences between groups [5,10,18].…”
Section: Discussionmentioning
confidence: 99%
“…* * Surgeries were all ACDF confirmed during the study by operative report and postsurgical radiographs. 6 Rehabilitation Research and Practice lumbar spinal stabilizer training combined with behavior or cognitive therapy) was included in several of these studies as behavioral or cognitive training has been shown to help improve recovery from spine surgery [12,37,38]. Given recent motor control studies specify 8 or more weeks necessary to integrate strength changes with spine stabilizers, so that 12 weeks may have not been a long enough follow-up time to see differences between groups [5,10,18].…”
Section: Discussionmentioning
confidence: 99%
“…Zudem konnte bei älteren Patienten eine geringere Schmerzlinderung nach lumbaler Wirbelsäulendegeneration festgestellt werden. Interessanterweise zeigte sich in einer Pilotstudie bei gebrechlichen Patienten, die unter dem Begriff "Frailty" zusammengefasst werden, dass sich diese Patienten von der Operation unbefriedigend erholen und über einen Zeitraum von über 3 Monaten relevante mentale und funktionelle Einschränkungen aufweisen [3].…”
Section: Alterunclassified
“…Rothrock et al [3] Schlechtere kognitive Erholung auch über einen Zeitraum von 3 Monaten nach elektiver WS-Operation bei "Frailty".…”
Section: Studie Kernaussageunclassified
“…While advanced age (>65 years) has been consistently identified as a risk factor for POCD (8, 14), the evidence is less convincing with other potential risk factors due to differences in populations and neurocognitive testing modalities (4, 7). For example, it has long been thought that preexisting frailty in general (1520), and neurocognitive frailty in particular (9, 21, 22) may be a risk factor for POCD as these patients may be vulnerable to cognitive insults at baseline. Indeed, observational studies have shown that surgery may precipitate further cognitive decline in patients with neurodegenerative disorders such as Alzheimer's disease (AD) (23), and biomarkers of AD such as the apolipoprotein E4 (APOE-4) genotype have also been associated with development of POCD in elderly patients (24, 25).…”
Section: Introductionmentioning
confidence: 99%